Participation of COX2/mPGES1/PGE2 in mouse and human endometrial stromal decidualization - Peng-Chao Wang; Jie Liu; Yue-Fang Liu; Yang Wu; Lin-Li Xue; Zhen-Shan Yang (BMC Veterinary Research)
Abstract Background Prostaglandin E2 (PGE2) is vital for embryo implantation and decidualization. Whether COX2/mPGES1/PGE2 pathway is essential for mouse and human decidualization remains unclear. Results This study showed that mPGES1 was highly expressed in the mouse uterus’s subluminal stromal cells at the implantation site. COX2-specific inhibitor Valdecoxib and mPGES1 selective inhibitor MK886 were used to analyze the roles of mPGES1 and COX2 during mouse and human decidualization. During mouse in vitro decidualization, decidua/trophoblast prolactin-related protein (Dtprp) expression was significantly suppressed by Valdecoxib and MK886. Under human in vitro decidualization, mPGES1 significantly increases, while both cPGES and mPGES2 remain unchanged. PGE2-mediated upregulation of insulin growth factor binding protein 1 (IGFBP1) was significantly inhibited by Valdecoxib and MK886. Conclusions Our findings suggest the involvement of COX2/mPGES1/PGE2 pathway in both mouse and human decidualization.